An outbreak of deaths associated with AMB-FUBINACA in Auckland NZ. (August 2020) - Morrow, Paul L; Stables, Simon; Kesha, Kilak; Tse, Rexson; Kappatos, Diana; Pandey, Rishi; Russell, Sarah; Linsell, Oliver; McCarthy, Mary Jane; Spark, Amy; Vertes, Dianne; Triggs, Yvonne; et al.
Abstract: Background: AMB-FUBINACA is a synthetic cannabinoid that has been associated with periodic outbreaks of acute poisonings, but few fatalities. In late May, June and July 2017 Auckland, New Zealand, experienced an outbreak of deaths associated with AMB-FUBINACA that continued at a rate of about 2–3 per month through February 2019. The aim of this study was to define the demographic, circumstantial, pathological and toxicological characteristics of this outbreak. Methods: All records of the Northern Forensic Pathology Service, Auckland Hospital, were reviewed in which the word "AMB-FUBINACA" was referenced, including initial police reports, autopsy reports and toxicology reports. Recorded data included age, sex, race/ethnicity, times and locations, cause of death, autopsy and toxicology findings, and a brief summary of the circumstances of death. Descriptive statistics were performed using IBM® SPSS® Statistics Version 24 and Microsoft® Excel® Version 14.7.2. Findings: Sixty-four cases were identified. One sudden infant death and five cases where cause of death was due to trauma were excluded. Of the remaining 58 cases, 88% were male. Mean age was 42 years. In 95% of the deaths, AMB-FUBINACA alone or in combination with alcohol or another drug was listed as the primary or contributory cause of death. In 41 cases postmortem blood concentrations of AMB-FUBINACA acid were available, ranging from <45 ng/mL to >1000 ng/mL, mean 229 ng/mL, median 140 ng/mL. Comorbidities identified included mixed intoxications (29%), heart disease (47%) and obesity (16%). A mental health diagnosis was reported in 50%, and 40% were on antipsychotic medications. Interpretation: This study presents characteristics, comorbidities and toxicological findings in a unique outbreak of deaths associated with the synthetic cannabinoid AMB-FUBINACA in Auckland, NZ. Funding: All work was funded as part of the usual employment of the authors in their respective institutions. No special funding sources are reported.